Data Warehouse Success Lead towards Supply Chain Efficiency - Roespinoedji, Djoko; Mudzakar, M. Kohar; Mulyawan, R. Ferry; Gusnandar, Sendi; Jaafar Sidik, Morni Hayati (ExcelingTech, 2019)
Data warehouse management is crucial challenge due to which most of the supply chain companies are facing the issues of data management. These challenges effect adversely on data warehouse success and ultimately effect negatively on supply chain efficiency. Different studies are carried out by different researchers on the area of supply chain, however, these studies are missing with the element of data warehouse management. Therefore, the objective of the study is to examine the factors that influence on data warehouse success and supply chain efficiency. Data were collected from warehouse employees working in Indonesian supply chain companies. Results of the study shows that data warehouse success is based on various factors such as system quality, information quality, service quality and relationship quality. These factors have positive association with data warehouse success and data warehouse success increases the supply chain efficiency. Thus, companies should focus on these elements to promote data warehouse success. This study is helpful for practitioners to promote supply chain efficiency through data warehouse success.